HOW TO INCREASE ACCESSIBILITY OF BIOMEDICAL INFORMATION? EDITORS' NETWORK INITIATIVE OF THE NATIONAL SOCIETY CARDIOVASCULAR JOURNALS OF THE EUROPEAN SOCIETY OF CARDIOLOGY - I. P. Kolos; D. A. Anichkov; R. G. Oganov (Столичная издательская компания, 2015)
.